BIMBINGAN BELAJAR MATEMATIKA TINGKAT SD - Harefa, Darmawan; Forilina Laia; Vira Febrian Lombu; Evan Drani Buulolo; Alena Zebua; Ofirna Andini Sarumaha; Agus Farin; Elvita Janratna Sari Dakhi; Vinxen Sians Zihono; Nariami Wau; Flora Melfin Sriyanti Duha; Statis Panca Putri Laiya; Lena; Nimarwati Laia; Martina Ndruru; Angelin Febrianis Fau; Adaria Hulu; Yulinus Halawa; Desrinawati Nehe; Jesika Bago; Odisman Buulolo; Sofiana Faana; Herlis Juwita Ndruru; Desiputri Hayati Giawa; Alexander Frisman Giawa; Anita Zagoto (Universitas Nias Raya, 2024)
The aim of this service is to provide study guidance to elementary school students. The service methods used are lectures and direct practice, how mathematics learning guidance can be given directly to students. results and benefits of service. Effective mathematics tutoring is able to create conducive active learning conditions, this is very good for the process of developing students' potential abilities optimally. Proper mathematics tutoring is able to provide changes in behavior and characteristics for the better, which will later be useful for students so that they can place themselves in the right situation. Assist in adjusting the process of learning activities and preparing learning programs for students so that academic potential can be achieved. Help teachers understand the characteristics of students and can direct students in developing their abilities and potential in accordance with the students' interests and talents. It becomes material for self-evaluation, whether the learning program and learning activities carried out are in accordance with the student's competency or not.